Pengaruh Literasi Keuangan dan Kontrol Diri terhadap Perilaku Menabung Mahasiswa Semester Akhir STIE Widya Praja Tanah Grogot - Rusmiati Rusmiati; Nuriyah Nuriyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the influence of financial literacy and self-control on the saving behavior of final-year students at STIE Widya Praja Tanah Grogot. Final-year students were selected as the focus of this study based on the consideration that this group is at a critical transitional phase from academic life to the workforce, making their financial readiness particularly relevant for examination. A quantitative research method with a survey approach was employed. The research sample consisted of 125 final-year students (semester 7 and semester 8) selected using purposive sampling technique. Data were collected through questionnaires measuring three main variables: financial literacy (10 items), self-control (10 items), and saving behavior (10 items) on a Likert scale of 1–5. Data were analyzed using multiple linear regression analysis with SPSS software. The results indicate that financial literacy has a positive and significant effect on saving behavior (β = 0.412; t = 5.231; p < 0.05). Self-control also has a positive and significant effect on saving behavior (β = 0.387; t = 4.876; p < 0.05). Simultaneously, financial literacy and self-control significantly influence saving behavior with a coefficient of determination (R²) of 0.563, meaning that both variables explain 56.3% of the variation in final-year students’ saving behavior. These findings imply that improving financial literacy and strengthening self-control are important strategies for enhancing students’ financial readiness prior to graduation.